Chylothorax after coronary artery bypass grafting: Is it always early?. Issue 9 (6th June 2021) - Kanna, Sharmil; Arora, Shashank; Goel, Himanshu; Jindal, Pramoj; Shad, Sujay
Abstract: Background: Chylothorax is a rare complication of cardiothoracic surgical interventions and usually presents early in the postoperative period. Materials and Methods: We present a case of 63 years female who presented with chylothorax 5 months after undergoing coronary artery bypass surgery. Discussion and Conclusion: Chylothorax should be considered in patients with recurrent pleural effusions even if the effusions do not have the typical milky appearance. Although chylothorax in most cases will present early in post operative period, it should be remembered that it can present in a delayed manner. Morbidity and health care costs associated with this entity can be remarkably high and therefore it is of great importance to diagnose and treat it.